Direct Cloning of a Xylanase Gene from Pawan-Riau Hot Spring - IS HELIANTI (Bogor Agricultural University, Indonesia, 2007)
A functional gene containing an Open Reading Frame (ORF) encoding a ?-1, 4-endoxylanase glycosyl hydrolase family 11 was cloned directly using metagenomic PCR-cloning method from Pawan Hot Spring sample in Riau. The gene consisted of 642 nucleotides, encoded for 213 amino acids. The amino acid sequence analysis using BLAST showed that the gene has high homology (93%) with xylanase gene from Bacillus subtilis. The gene showed its function when it was subcloned into an expression vector and overexpressed in E. coli. The crude extract of the recombinant enzyme had activity for 170 U/ml at 50 oC. The result of this work showed that metagenomic approach was a powerful short cut method to obtain recombinant biocatalyst that was useful for industrial application. Key words: ?-1, 4-endoxylanase, metagenomic DNA, Pawan-Riau hot-spring